Municipal solid waste management in South Africa: evaluation of waste to energy technologies for generating electricity from municipal solid waste, Gauteng Province - Dlamini, Smangele Qondile (My University, 2019)
“Waste-to-energy” technologies have been presented as one of the avenues to improve the management of solid waste through the recovery of waste whilst promoting a clean urban environment and increasing renewable energy generation. The Gauteng province, however, is still high and solely dependent on landfills for municipal solid waste management. Because of the concern on the depletion of the City of Johannesburg’s landfills airspace by the year 2023, increasing waste generation and greenhouse gases emission, the province has an urgent need for a better waste management strategy. This projection becomes a motivation for the identification of suitable waste-to-energy alternative avenues to manage waste in the province. This study evaluated the potential of municipal solid waste for electricity production in nine municipalities in the Gauteng province using landfill gas to energy, incineration and anaerobic digestion technologies as well as the economic viability of the waste-to-energy technologies. The LandGEM equation was used to estimate methane generation from the waste generated in each year in order to evaluate the electricity generation potential of the technologies. The levelised cost of energy, net present value and payback period methods were used to determine the economic viability of the technologies. The study also evaluated the global warming potential, acidification potential and dioxin/furan emission potential of the waste-to-energy technologies using the life cycle assessment methodology. Four scenarios were evaluated, namely scenario 1- landfill, scenario 2 - landfill with energy recovery, scenario 3 - incineration with anaerobic digestion and scenario 4 - incineration with landfill with energy recovery. Key findings revealed that the City of Johannesburg municipality has the highest waste generation potential of 2.18925×109 – 3.9103×109 kg/yr between the years 2016 to 2035 with methane generation estimates of 181700000 m3/yr (12210 ft3/min). The incineration technology is the next best and appropriate technology option for municipal solid waste management in the province in terms of waste recovery and electricity generation potential. However, from an economic point of view, anaerobic digestion technology presented itself as an economically viable waste-to-energy technology with the lowest payback period compared to landfill gas to energy technology and incineration technology. Scenario 3 (incineration with anaerobic digestion) has the highest greenhouse gas emissions in all the municipalities. This was expected as the electricity generation potential for incineration was high in all the municipalities followed by the anaerobic digestion technology with high methane generation during biological degradation of organic waste. Scenario 4 (incineration with landfill gas to energy) has the highest acidification potential compared to the other scenarios. Dioxin emission in scenario 4 (incineration with landfill gas to energy) was higher than that in scenario 2 (landfill gas to energy) and it was not surprising as dioxin are emitted through the combustion of waste. This study is very useful to policy makers, scientists and investors for decision making purposes as it could lead to optimal investment in waste-to-energy technologies.
Thesis submitted in fulgilment of the requirements for the Degree of Doctor of Philosophy in Geography and Environmental Studies at the University of the Witwatersrand, October 2019
Keywords: Renewable energy sources; Water reuse; Waste minimization